ANALYSIS OF ILLOCUTIONARY SPEECH ACTS IN THE FILM NORAH - Muhammad Nashi Huddin Ubaidillah; Rima Mella; Khusnul Fatimah; Zulfan; Khairawati (PT. Jurnal Center Indonesia Publisher, 2026)
This study investigates the forms and functions of illocutionary acts in the film Norah (2023) using a qualitative descriptive approach. The research problem centers on how dialogic interactions and rural Saudi socio-cultural contexts shape the distribution of illocutionary types. Data were collected via observation and note-taking, then classified according to Searle’s five categories (assertive, directive, commissive, expressive, declarative) and analyzed through three stages: data collection, analysis, and presentation. The findings reveal that illocutionary speech acts in the film Norah are dominated by directives in the form of commands, prohibitions, and invitations, which highlight the speaker’s role in controlling actions. In addition, expressive and commissive acts appear in the form of advice, requests, and polite expressions that function to maintain harmony and interpersonal closeness. Overall, the use of illocutionary acts in the film reflects social relations and the dynamics of everyday interaction in rural Arab society.